Rolling audit on the quality of discharge summary in TU Teaching Hospital - Guragain, RPS; Adhikari, P (Journal of Institute of Medicine Nepal, 2009)
Background: Audit 2007 (December) was significant in that it was the third rolling audit on the discharge performance started in TU Teaching Hospital. The audit was started in 2005 and it intends to transfer important clinical information from inpatient to outpatient settings and between hospital admissions. Materials and Methods: There were 20 discharge summary forms picked up from each of seven departments of TU Teaching Hospital between November 2007 and December 2007. All summaries were looked for the inclusion of modified Van Walraven criteria. Apart from Van Walraven eight points, admission and discharge date and follow up instructions were also checked by the second author. These summaries were compared with previous discharge summary performed 2 ½ years ago. Results: Department of ENT and HNS showed the best discharge summary as per modified Van Walraven criteria whereas Department of Orthopaedics had the least inclusion of criteria. Previous study showed best summaries in Department of Gynaecology while poor in Department of Orthopaedics. Regarding completeness of hospital discharge summary form, Department of ENT and HNS had the highest number of almost completely filled discharge summaries (>90%) while Department of Medicine had the least number of properly filled discharge summaries. Previous audit showed Department of ENT and HNS to be the best while Department of orthopaedics to be the worst. On analyzing the previous recommendations, they were not properly followed. Conclusion: Discharge summary should be filled up completely without missing necessary information. Although ENT and HNS has best discharge summary according to Van Walraven discharge criteria as well as completeness of our hospital discharge summary, it needs to follow previous recommendations. The recommendations previously given should be strictly followed and informed to the heads of all Departments concerned. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 3-6